2017
DOI: 10.1128/mbio.00857-17
|View full text |Cite
|
Sign up to set email alerts
|

Leucine Biosynthesis Is Involved in Regulating High Lipid Accumulation in Yarrowia lipolytica

Abstract: The yeast Yarrowia lipolytica is a potent accumulator of lipids, and lipogenesis in this organism can be influenced by a variety of factors, such as genetics and environmental conditions. Using a multifactorial study, we elucidated the effects of both genetic and environmental factors on regulation of lipogenesis in Y. lipolytica and identified how two opposite regulatory states both result in lipid accumulation. This study involved comparison of a strain overexpressing diacylglycerol acyltransferase (DGA1) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 36 publications
3
20
1
Order By: Relevance
“…In all organisms from yeasts to mammals, the TORC1 pathway controls growth in response to nutrients such as leucine. This amino acid is capable of activating TORC1 kinase, resulting in GCN4 repression and prevention of TOR-dependent mGCN4 translation (Valenzuela et al 2001;Kingsbury et al 2015;Kerkhoven et al 2017). This contention is also supported by the herein presented observation that, in the presence of VIL, Gcn4myc 13 is poorly immunoprecipitated to the BAT1 and HIS4 promoters ( Figure 4C) as compared to that observed on glutamine or GABA, suggesting a low Gcn4 concentration when cells are grown on VIL.…”
Section: Under Biosynthetic Conditions (Glutamine) Leu3 Activates Batsupporting
confidence: 81%
“…In all organisms from yeasts to mammals, the TORC1 pathway controls growth in response to nutrients such as leucine. This amino acid is capable of activating TORC1 kinase, resulting in GCN4 repression and prevention of TOR-dependent mGCN4 translation (Valenzuela et al 2001;Kingsbury et al 2015;Kerkhoven et al 2017). This contention is also supported by the herein presented observation that, in the presence of VIL, Gcn4myc 13 is poorly immunoprecipitated to the BAT1 and HIS4 promoters ( Figure 4C) as compared to that observed on glutamine or GABA, suggesting a low Gcn4 concentration when cells are grown on VIL.…”
Section: Under Biosynthetic Conditions (Glutamine) Leu3 Activates Batsupporting
confidence: 81%
“…It presents several advantages as industrial host, including a vast repertoire of molecular tools and the ability to grow naturally in low cost substrates such as glycerol or molasses (Ledesma‐Amaro & Nicaud, ), or once engineered in xylose, raw starch, cellobiose, cellulose, or inulin (Guo et al, ; Ledesma‐Amaro, Dulermo, & Nicaud, ; Ledesma‐Amaro, Lazar et al, ; Wei et al, ; Zhao, Cui, Liu, Chi, & Madzak, ). Moreover, its metabolism, specifically the lipid metabolism, has been widely studied and characterized (Dulermo, Gamboa‐Melendez, Ledesma‐Amaro, Thevenieau, & Nicaud, ; Dulermo, Gamboa‐Melendez, Ledesma‐Amaro, Thevenieau, & Nicaud, ; Kerkhoven et al, ; Kerkhoven, Pomraning, Baker, & Nielsen, ; Qiao, Wasylenko, Zhou, Xu, & Stephanopoulos, ; Wasylenko, Ahn, & Stephanopoulos, ). Interestingly, lipid biosynthetic pathway and carotenoid pathway share a common precursor, Acetyl‐CoA, which is highly available in Y. lipolytica .…”
Section: Introductionmentioning
confidence: 99%
“…From our studies, it is not clear whether P ALK1 activates gene expression in S. cerevisiae. In a previous study 27 it has been shown that the expression level of ALK1 gene in nitrogen limiting conditions is comparable to the average expression of all other genes, which might indicate that there is some basal activity of the ALK1 promoter in its native host. We did, however, not observe any basal activity above the background level.…”
Section: Discussionmentioning
confidence: 90%